Productivity and profitability of peanut at various land suitability in North Lombok Regency of Nusa Tenggara Barat Province - Ahmadi Suriadi; Fitria Zulhaedar; Moh. Nazam (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
Peanuts (Arachis hypogaea L.) are the second main commodity in the annual cropping pattern in lowland and dryland in North Lombok District of NTB Province. However, peanut productivity is still low, and it varies across regions, which might be due to the traditional crop management of farmers and the difference in land suitability classes. Effects of crop varieties and land suitability on the peanut productivity have not been evaluated in the Region. Thus, this study aimed to evaluate the productivity and profitability of peanut varieties at various land classification in KLU NTB. The experiment was arranged in a Split Plot Design consisting of three classes of land suitability as main plot and six peanut varieties as sub-plot with three replications. The results showed that the land suitability classes have a significant effect on the agronomic variables of peanut varieties, including plant height, number of branches, number of pods and productivity. The highest peanut yield was obtained at suitable land class (S1), followed by moderately suitable land class (S2) and marginally suitable land class (S3) at 2.37 ton.ha-1, 2.08 ton.ha-1 and 1.71 ton.ha-1, respectively. Likewise, the R/C ratio follows a similar pattern to productivity in various land suitability classes. The highest yield (above 2 ton.ha-1) in each land suitability class was produced by Kelinci variety, followed by Tuban, Bima and Talam varieties. Those varieties have potential prospective to be developed in North Lombok Regency.